2019
DOI: 10.1111/pbr.12700
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population structure and key phenotypic traits driving variation within soyabean (Glycine max) collection in Ghana

Abstract: Soybean [Glycine max (L.) Merrill] is an important oilseed crop worldwide and it has recently become the crop of interest in Ghana. In this study, 142 soybean accessions were genotyped with 34 SSR markers and concurrently evaluated for five quantitative and two qualitative phenotypic traits. Twenty‐nine of the SSR markers were polymorphic with mean allele number of 5.3, polymorphic information content (PIC) of 0.51 and gene diversity of 0.55. Molecular analysis based on unweighted paired group arithmetic mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Pod yield, kernel yield and, late leaf spot, rust scored, and shelling percent are important yield components that can be used for indirect selection for yield due to their significantly correlation with yield. The correlations found in this study were in concurrence with Denwar et al ( 2019 ), who also found that disease ratings were negatively correlated with yield while selection for number of pods and seeds per pod increased grain yield in soybean. The positive correlation between rust and late leaf spot shown in this study were confirmed in the previous reports (Narasimhulu et al .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Pod yield, kernel yield and, late leaf spot, rust scored, and shelling percent are important yield components that can be used for indirect selection for yield due to their significantly correlation with yield. The correlations found in this study were in concurrence with Denwar et al ( 2019 ), who also found that disease ratings were negatively correlated with yield while selection for number of pods and seeds per pod increased grain yield in soybean. The positive correlation between rust and late leaf spot shown in this study were confirmed in the previous reports (Narasimhulu et al .…”
Section: Discussionsupporting
confidence: 91%
“…This showed that most genotypes were more inclined towards susceptibility rather than resistance. Similarly, (Denwar et al 2019 ) found that trait contribution to different PCs differed depending on the extent of variation for the particular trait among test genotypes. Pod yield, kernel yield and, late leaf spot, rust scored, and shelling percent are important yield components that can be used for indirect selection for yield due to their significantly correlation with yield.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The mean gene diversity of 0.42 recorded in this study is higher than that of Liu et al [30] who reported a mean gene diversity of 0.35 using 5195 SNP markers to screen 577 soybean accessions. Nonetheless, it is lower compared to the 0.78 and 0.55 reported by Abe et al [31] and Denwar et al [32], respectively, in soybean using microsatellite (SSR) markers. The lower gene diversity with SNP markers is due to their bi-allelic nature when compared with multi-allelic markers such as SSR, as theoretically, maximum gene diversity observable with biallelic markers is 0.5.…”
Section: Discussionmentioning
confidence: 67%
“…Genetic heritable variability is indispensable in plant breeding aimed at developing new cultivars that express desirable characteristics generation after generation [13]. Furthermore, the development of improved varieties is enhanced when parents are selected based on genetic heterogeneity [14], making genetic variation estimation necessary in breeding programs to allow the selection of parental lines either to increase breeding population variation or to develop hybrids for cultivar release [15].…”
mentioning
confidence: 99%